THE INFLUENCE OF BUSINESS STRATEGY, SUPERVISORY EFFECTIVENESS AND SUSTAINABLE GROWTH RATE IN BANKRUPTCY PREDICTION - Asmarani, Niken Yulika; Murtanto, Murtanto (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
This research aims to test and prove how influence business strategy, supervision effectiveness and sustainability growth level have in predicting bankruptcy. The research is quantitative research, which uses a panel data regression analysis model. The research sample is companies that are included in the special monitoring category of the Indonesia Stock Exchange in April 2024, with PKPU status or have negative equity in companies operating in the property and real estate industry. The results of the research show that business strategy, supervision effectiveness and the level of sustainability growth of a company have a significant influence of 49% in predicting bankruptcy of companies in the property and real estate industry in the 2019 - 2023 research period. Meanwhile, business strategy and supervision effectiveness have a positive influence. against Financial Distress. Meanwhile, the Sustainability Growth Rate has a negative effect on Financial Distress, where the more a company does not experience sustainability, the closer it is to the bankruptcy area. Meanwhile, firm size as a control variable in this study does not have a significant effect on Financial Distress.